LEXICAL MEANING AND CULTURAL ADAPTATION ON THE PRODUCT OF NESTLE DANCOW - I Gusti Agung Istri Aryani; Sri Widiastutik (Balai Bahasa Provinsi Bali, 2017)
AbstractCommonly, an amazing and attractive advertisement intends to hypnotize their target consumer in seeing, reading, or even hearing the ads continually. Besides, the power of persuading and motivating in messages from the way of informing product benefit could also give impact to buyer in deciding to buy the product. This research discusses the contexts of advertising found on packages of two Nestle products, especially Nestle Dancow Actigo and Nestle Dancow Enrich. These products were analyzed based on pictures or symbols and text found on packages. It is aimed at finding out the context of discourse advertising on those packages. Data were collected from analysis of text, including pictures or symbols and additional questionnaires distributed to 50 respondents located at Denpasar and Gianyar. Urban society were used to evaluate concerning on their understanding of English even though Indonesian language mostly applied on packages of products. Method used in analyzing data is descriptive qualitative and quantitative with simple statistics and explanation. It showed that connotation and denotation meanings highlighted lexical items and its cultural adaptation using process of copy adaptation to fit the culture of their targeted consumers. Means found 6 words or phrases of English from 10 of them on packages understood by 50 respondents as of: 35 for Full Cream as highest score and 16 respondents for FortiGro as the lowest score. In addition, brand name, symbol and images showed producer seemed to have close relationship with consumer and able to attract target consumer attention as majority of findings. It can be concluded that ads on packages of Nestle Dancow had succeeded to be understood by the society through the messages implied.